The polysemy of Public Governance in Tourism studies: a systematic review - Mediotte, Elias José; Emmendoerfer, Magnus Luiz; Oliveira, Guilherme de Avelar (Revista Turismo em Análise, 2020)
Although literature points out that there is a growing debate at the Public Governance field about planning and implementing policies involving Public Administration and Stakeholders, studies aimed at tourism, especially about the conceptual aspects of that theme, are limited. This article proposes to understand the discursive formations related to the academic community’s understanding of the concept of Public Governance in the tourism sphere. It presents bibliographical perspectives on New Public Governance, New Public Management, and Tourism. The Concepts of Governance from 21 academic papers are discussed and analyzed through a systematic review based on a qualitative exploratory-descriptive approach. The results show that, for the majority of the analyzed academic works, Public Governance in tourism is characterized as a normative economic paradigm and as a promoter of public-private partnerships. We conclude that there is a successive disharmony among the concepts related to Public Governance at Tourism. It happens due to the inclination of public management towards the eminent managerial bases prescribed by the New Public Management, in detriment to the co-production of collective actions, with an expressive performance of the civil community in this, that reflects the real proposition of New Public Governance.